Psychoanalytic psychotherapy and cognitive-behavioral therapy: is it possible an integration into clinical practice? (Research, Society and Development, 2022)
Integrative psychotherapy aims to articulate theoretical and methodological knowledge from more than one approach, taking advantage of its potentialities in a complementary way for better treatment effectiveness. This practice has been applied internationally, but much in Brazil. This experience report aims to discuss the possibility of integration between psychoanalytic psychotherapy and cognitive-behavioral therapy based on the analysis of a clinical case. The psychotherapy happened in 2017, totalizing twenty sessions. After the analysis of patient care it was possible to observe that, although each of the theoretical approaches have different methods, both have a mutual goal, which is the emotional well-being of the patient through the development of strategies to deal with their difficulties. It was concluded that the integration of the two approaches in a complementary way and non-reductionist manner might be valuable for clinical application. Studies that show integrative methods and support these approaches on psychotherapeutic practice should be encouraged.